(untitled) (Asian Journal of Pharmaceutics (AJP), 2021)
Aim: The objective of this study was to develop a novel self-nanoemulsifying drug delivery system (SNEDDS) which produced very small and uniform emulsion droplets, resulting in enhanced solubility, dissolution, and oral bioavailability of poorly water-soluble rosuvastatin (RST) calcium. Materials and Methods: The effects of oil, surfactant, and cosurfactant on the drug solubility were assessed, and pseudoternary phase diagrams were plotted. Among the liquid SNEDDS formulations tested, the liquid SNEDDS composed of cinnamon oil (oil), Cremophor EL (surfactant), and transcutol P (cosurfactant) at a ratio of 2:1 (Smix) and 1:5 (oil:Smix) ratio, produced the smallest emulsion droplet size. The RST-loaded liquid SNEDDS formulation was assessed for the emulsion droplet size, solubility, and dissolution of the emulsified SNEDDS and compared to the pure drug. Different SNEDDS formulations of RST calcium were prepared by aqueous phase titration method. Selected formulations were characterized in terms of self-emulsification time, cloud point temperature, drug content, and particle size. Finally, selected SNEDDS (F1–F8) was subjected to in vitro dissolution/drug release studies. Results and Discussion: Droplet size of formulation F5 was found to be lowest as compared to other formulations. In vitro drug release studies showed 98.3% release of drug from optimized formulation, which was found to be much faster than marketed RST calcium. Conclusion: Thus, this novel SNEDDS developed represents a potentially powerful oral delivery system for RST calcium to enhance solubility and thereby bioavailability.